(untitled) (Journal of Multidisciplinary Sciences and Innovations, 2025)
This article provides a comprehensive analysis of improving management efficiency in the customs system of Uzbekistan through the application of digital technologies. The purpose of the study is to assess the current state of digital transformation in customs administration, analyze the dynamics of trade facilitation indicators, and identify priority directions for enhancing management efficiency based on international best practices. The research employs methods of analysis and synthesis, comparative analysis, statistical analysis, and logical generalization. Based on data from the UN Global Survey on Digital and Sustainable Trade Facilitation, the study examines the progress achieved in the digitalization of Uzbekistan’s customs system during 2015-2025 and identifies existing challenges through a comparative analysis with South Korea and Kazakhstan. The findings demonstrate that digital technologies should be implemented not as isolated initiatives, but as an integrated strategic management model. The article proposes practical and policy-oriented recommendations aimed at strengthening inter-agency digital integration, adopting data-driven decision-making models, minimizing the human factor, and enhancing digital competencies of customs personnel. The results of the study have significant practical implications for improving customs governance and increasing the country’s competitiveness in international trade.